THE DYSPHAGIA INVESTIGATION: IS THERE STILL SPACE FOR THE VIDEOFLUOROSCOPIC METHOD? - Charles Henrique Dias MARQUES; Luiz João ABRAHÃO-JÚNIOR; Eponina Maria Oliveira LEMME (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2022)
ABSTRACT - BACKGROUND: Dysphagia can lead to aspiration pneumonia, impacting the nutritional status and quality of life of the patient. The videofluoroscopy is highlighted for allowing both a real-time evaluation and the recording of the images for later review and analysis. AIM: This study aimed to describe the characteristics of the population referred for videofluoroscopy and its value as an investigation method. METHODS: A descriptive and retrospective study was conducted. Exams were analyzed in lateral and anteroposterior views and reviewed using the frame-by-frame analysis software. The variables analyzed were an indication of the exam, previous diseases, dynamics of the oral and pharyngeal phases, and the degree of penetration/aspiration. RESULTS: A total of 141 exams were analyzed. The study population had a median age of 66.24±17.78 years. For the indication of the exam, the investigation of dysphagia was highlighted (n=87, 61.7%) and for previous conditions, diverticulum (n=13, 9.2%), pharyngeal bar (n=12, 8.51%), and stroke and Parkinson’s disease (n=9, 6.4%) were highlighted. In the oral phase, 45 (31.9%) patients had a premature loss, and 108 (76.6%) patients had normal transit time. However, 100 (70.9%) had inadequate ejection. In the pharyngeal phase, 119 (84.4%) had efficient laryngeal displacement and 107 (75.9%) had an adequate opening of the upper esophageal sphincter. The beginning of the pharyngeal phase was classified as inadequate in 131 (92.9%) patients, and 80 (56.74%) had pharyngeal residue. Notably, 100 (70.9%) patients had grade 1 on the penetration/aspiration scale. CONCLUSION: Despite the didactic division of phases, swallowing is complex and has transition stages. Videofluoroscopy is the only method for evaluating all phases of swallowing and its events.